2010
DOI: 10.2190/tw.40.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Technical Communication Internship Requirements in the Academic Economy: How We Compare among Ourselves and across other Applied Fields

Abstract: This article reports a study of internship requirements in technical communication programs compared with three established professions and one emerging profession that have certification or licensing requirements for practitioners. The study addresses three questions about technical communication internship programs: 1) Are internships offered as a way to fulfill program academic credit requirements? 2) If internships are offered, are they required or elective? 3) What are the minimum/maximum academic credits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…328.) Savage and Seible (2010) also note the importance of professional-level work in the internship as evaluated by professionals in the field. Clearly, professionalism is an important component of the internship experience to industry mentors.…”
Section: Industry Mentorsmentioning
confidence: 97%
See 3 more Smart Citations
“…328.) Savage and Seible (2010) also note the importance of professional-level work in the internship as evaluated by professionals in the field. Clearly, professionalism is an important component of the internship experience to industry mentors.…”
Section: Industry Mentorsmentioning
confidence: 97%
“…The literature has explored ways to ensure that these internships are quality experiences for students, from required number of hours (Savage & Seible, 2010) to practitioner surveys (Jennings, 2012; Sapp & Zhang, 2009) to intern case studies (Bourelle, 2014; Smart & Brown, 2002). Kohn (2015) has suggested that part of successful mentoring is the scaffolding by both academics and industry professionals for workplace tasks.…”
Section: Internships In Technical and Professional Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is only with more reported success stories of internships that we can move forward toward the standards Savage and Seible suggest are missing [18]. I urge readers to consider the undertaking of linked courses and internships, writing and publishing reports of the challenges they have faced, but most of all, of the successes they have encountered, no matter how small.…”
Section: The Technical Communication Internship / 187mentioning
confidence: 99%